2012
DOI: 10.5194/acp-12-11417-2012
|View full text |Cite
|
Sign up to set email alerts
|

A new scheme for sulphur dioxide retrieval from IASI measurements: application to the Eyjafjallajökull eruption of April and May 2010

Abstract: Abstract.A new optimal estimation algorithm for the retrieval of sulphur dioxide (SO 2 ) has been developed for the Infrared Atmospheric Sounding Interferometer (IASI) using the channels between 1000-1200 and 1300-1410 cm −1 . These regions include the two SO 2 absorption bands centred at about 8.7 and 7.3 µm (the ν 1 and ν 3 bands respectively). The retrieval assumes a Gaussian SO 2 profile and returns the SO 2 column amount in Dobson units and the altitude of the plume in millibars (mb). Forward modelled spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 49 publications
2
129
0
Order By: Relevance
“…The method for retrieving near-surface SO 2 concentrations in Norilsk from IASI measurements is largely based on the one presented in Carboni et al [2012]. It relies on the optimal estimation framework [Rodgers, 2000], which traditionally consists of simultaneous iterative adjustment of the atmospheric parameters of interest and spectrally interfering unknown variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method for retrieving near-surface SO 2 concentrations in Norilsk from IASI measurements is largely based on the one presented in Carboni et al [2012]. It relies on the optimal estimation framework [Rodgers, 2000], which traditionally consists of simultaneous iterative adjustment of the atmospheric parameters of interest and spectrally interfering unknown variables.…”
Section: Methodsmentioning
confidence: 99%
“…While complete information on these interfering unknowns is not available, often there is some a priori information. To exploit this, a generalized covariance matrix can be constructed from the difference between observed spectra and forward simulated spectra (see Carboni et al [2012] for details). In this way, a mean difference and associated covariance matrix can be calculated, representative for our missing information on the interfering unknowns (these include the IASI noise, forward model errors, errors in the meteorological fields, and errors coming from the lack of knowledge of the parameters affecting radiance spectra).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent papers (Clarisse et al, 2012(Clarisse et al, , 2014Carboni et al, 2012) have demonstrated the potential of the IASI instrument to provide useful SO 2 measurements. In particular, Clarisse et al (2014) files with plume heights estimated from IASI and find very good agreement.…”
Section: Iasimentioning
confidence: 99%
“…In this work the Oxford-RAL Retrieval of Aerosol and Cloud (ORAC) algorithm (Thomas et al, 2009a;Poulsen et al, 2012) and the use of a generalized error covariance matrix, successfully applied to the retrieval of volcanic SO 2 by Carboni et al (2012), are adapted for use with volcanic ash. The method uses an optimal estimation retrieval algorithm to obtain probable values for the ash optical depth (AOD), particle effective radius, plume top height, and effective radiating temperature.…”
Section: Introductionmentioning
confidence: 99%